The Organisation of Audio-Visual resources for learning: in a local education authority - S. M., Ed Smith; Central committee of advisers in audio-visual education; Central committee of teachers' audio-visual aids groups (London National committee fot audio-visual aids education, 1970)
The last few years have seen a change in the attitudes of teachers and local education authorities in Great Britain generally toward the use of audiovisual media as instructional aids. This booklet provides a concise account of the broad general principles to be considered in setting up and running an audiovisual resources center within a local education authority in Great Britain. Included in the consideration are the functions and responsibilities of advisory services; duties of local education authority audiovisual resources centers such as evaluation, provision of information and services, staffing, and equipment purchasing; and the organization of audiovisual resources for learning in secondary schools with information on staffing, equipment and materials, and accommodations. (Sh)
Keywords: Educational Resources